Effect of green tea extract addition on antioxidant activity, physicochemical, and organoleptic properties of functional beverages - Hari Hariadi; Adhi Susilo; Eko Yuliastuti Endah Sulistyawati; Athiefah Fauziyyah; Yusep Ikrawan; Judiono Judiono (Open Global Scientific Journal, 2023)
Antioxidants are compounds that can capture free radicals. Green tea is an herbal beverage that contains antioxidants. Non-dairy creamer is an additive made from vegetable oil. Green tea can be made into powdered instant beverages with the addition of non-dairy creamer. This study aimed to determine the effect of the addition of green tea extract on organoleptic properties, acceptability, antioxidant content, nutritional content, and the results of the economic value of non-dairy creamer functional beverage products. The research design used was a complete randomized design (CRD) using three treatments, namely the addition of 0.8 g, 0.9 g, and 1.0 g of green tea extract, with three replications. Organoleptic test was conducted on each treatment to determine the best treatment in terms of taste, color, and aroma. Antioxidant activity test was also performed on each treatment. A proximate test was then conducted on the best treatment to determine the nutritional content. The results reveal that the addition of green tea extract has generated a significantly different effect on organoleptic properties and antioxidant activity in non-dairy creamer functional beverages. The best treatment was F1, namely the addition of 0.8 g green tea extract, which has generated results in the form of color 4.05, taste 5.67, aroma 4.15 on a scale of 1–7, then antioxidant activity of 4,973.53 ppm, water content 1.42%, ash content 1.35%, protein content 2.30%, fat content 2.13%, and carbohydrates 90.52%.